Desenvolvimento, caracterização e avaliação de nanocápsulas poliméricas contendo sinvastatina na prevenção da fibrose peritoneal - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
Introduction: peritoneal dialysis causes changes in the peritoneum, which can take severe forms, which can bring risk to the patient. Some drugs, including statins, may eventually prevent damage, but there are no studies using nanotechnology to improve the action of drugs. Objective: To develop and characterize simvastatin nanocapsules and to study the influence of their use on peritoneal fibrosis induced in rats by the use of glucose-rich peritoneal dialysis solution. Methods: Simvastatin nanocapsules were developed using a preformed polymer interfacial deposition method, which were characterized by Fourier Transform Infrared Spectroscopy, Field Emission Gun Scanning Microscopy, X Ray Diffraction, Zeta Potential, measurement of the particle size, encapsulation efficiency and in vitro release profile. Next, a prospective controlled in vivo study was performed on non-uremic Wistar rats. 48 animals were studied, divided into 4 groups: sham, peritoneal dialysis, peritoneal dialysis with conventional simvastatin, peritoneal dialysis using polymeric nanocapsules containing simvastatin. The animals were submitted to abdominal puncture daily, and a peritoneal dialysis solution was infused with 4.25% glucose. The degree of fibrosis and the expression of TNF-α and Interleukin-6 were evaluated. Results: The method of obtaining nanocapsules achieved an incorporation greater than 99%. In the animal study, the analysis showed that TNF-α expression and fibrosis intensity were significantly less intense in the group using SV nanocapsules. Conclusion: a study showed that the method is capable of forming simvastatin nanocapsules, and that their use reduces peritoneal inflammation induced by dialysis solution.
Keywords: Fibrose peritoneal; Diálise peritoneal; Sinvastatina; Nanocápsulas; Interleucina 6; TNF-α; Peritoneal fibrosis; Peritoneal dialysis; Simvastatin; Nanocapsules; Interleukin 6; TNF-α; CNPQ::CIENCIAS DA SAUDE::FARMACIA